Entry point into new trimeric and tetrameric imide‐based macrocyclic esters derived from isophthaloyl dichloride and methyl 6‐aminonicotinate. (1st January 2013) - Mocilac, Pavle; Gallagher, John F.
<x xml:space="preserve">Abstract</x> The one‐step reaction of isophthaloyl dichloride with the 2‐aminopyridine derivative (methyl 6‐aminonicotinate) yields (i) a trimer‐based macrocycle (EsIO)3 and (ii) a tetramer‐based macrocycle (EsIO)4 in modest isolated synthetic yields (total of 25%), together with (iii) longer open‐chain oligomers. The macrocyclization relies on the semi‐flexible imide hinge formed by reaction of the 2‐amino(pyridine) functional group with two acyl chloride functional groups. The determining factors in macrocycle synthesis are: (a) imide formation using the heteroaromatic ortho‐N functionality; (b) the inherent ability of the imide to twist by 85–115° from planarity (as measured by the CO...CO imide torsion angles), thereby providing a hinge for macrocyclic ring closure or potentially (non)helical assembly in oligomer/polymer formation; (c) the conformational flexibility of the isophthaloyl group with meta‐related carbonyl groups to twist and adopt either syn or anti conformations, although the syn conformation is observed structurally for all isophthaloyl groups in both (EsIO)3 (trezimide) and (EsIO)4 (tennimide) macrocycles.